(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Collective memory is usually an object of concern and analysis in times of resolution of violent social conflicts.The forms taken by such processes of remembering are multiple and include the construction of semiotic-material narratives produced in relation to places of memory and formed by the selection, statement and omission of different events. In the interepretations they arouse, memory strategies that in- volve a complex grid with meanings of the past are adopted. They are, also, materialized in the public sphere. This arti- cle analyzes and questions some of the narratives produced within diverse fields of research on post-dictatorial Chile